PENEGAKAN HUKUM PELANGGARAN LALU LINTAS MENGANGKUT PENUMPANG LEBIH DARI SATU ORANG DALAM KENDARAAN RODA DUA OLEH KEPOLISIAN RESOR KOTA PAYAKUMBUH - Muhammad Hafizh; Mukhlis R; Elmayanti Elmayanti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2020)
In modern times, human activities are greatly helped by technology that facilitates the movement of each individual. So the existence of two-wheeled vehicles or motorbikes makes it easier for people to move from one place to another. A motorcycle is a motorized vehicle with two or three wheels, without a house, with or without side buggies. The impact of carrying more than one passenger in a two-wheeled vehicle can endanger the motorcyclist and other traffic users, it can also be detrimental to pedestrians around the traffic and this is dangerous. This research is an empirical sociological research. This research was conducted in the legal area of Payakumbuh City. firstly, law enforcement against violations of carrying more than one passenger in a two-wheeled vehicle in Payakumbuh City is still not being realized properly, in carrying out its role to enforce the law in the community, law enforcers must also pay attention to norms. norms or rules that must be obeyed by law enforcers or maintenance.These norms need to be obeyed, especially in carrying out the law, drafting and maintaining the law. The inhibiting factor for law enforcement to carry more than one passenger in a two-wheeled vehicle is cultural factors and factors of law enforcement officials, such as cultural factors that should ride a motorbike by carrying more than one person is not a culture in Payakumbuh City, lack of coordination between the community and law enforcement officers, the lack of human resources owned by law enforcement officers.Keywords: law enforcement – two wheeled vehicle - Payakumbuh Police Resor